Association between prematurity and feeding difficulties in infancy: systematic review (Research, Society and Development, 2022)
Objective: to perform a systematic review of the literature to analyze the hypothesis of association between prematurity and eating difficulties in childhood. Methods: the systematic review was conducted according to the PRISMA guidelines. The research was conducted by two independent researchers on PubMed and SciELO databases using the following combined keywords: “premature infants", “premature newborn”, “preterm”, “eating disorders”, “eating disorders in childhood”, “eating behavior”, “disease in premature infants”, “nutritional disorders of nursing infants", and its correlates in Portuguese. Articles published from 1996 to 2022 were included in our review. Results: of the 45 eligible articles, 21 were included in the review. 19 studies (90,5%) associated prematurity to a risk factor for the development of eating difficulties in childhood. The main eating difficulties were related to introduction of solid diet, oral motor difficulty, refusal/avoidance of food, coughing, vomiting, appetite and pleasure in eating reduced, disorganized or dysfunctional feeding, greater selectivity, food neophobia, and poorer feeding compared to children at term. Ten studies (47,6%) indicated that the lower the gestational age and the lower the birth weight, the higher the prevalence of eating difficulties. Conclusions: There is important evidence associating prematurity to specific eating difficulties in childhood. However, the methodological weaknesses of the studies included in our review decrease the quality of the evidence produced.